Autorytet i wartości u stóp - Witkowski, Lech (Er(r)go. Teoria - Literatura - Kultura, 2013)
Lech Witkowski Authority and Values at One’s Feet The author attempts to summarize his own discussions from previous books devoted to the category of authority in social practice, symbolic culture, and in the history of humanities and social sciences. He emphasizes the idea of treating every place that can implement the reference to authorities as being at every man’s feet, at hand. Such perspective invalidates the view of authority in terms of a highly dominating point of reference, or a guarantee of certainty which relieves us from the effort of our own investigations, and points out the illusion of treating authority only in terms of a distanced repetition of erudite associations. What matters is the value of a real encounter with the life-giving symbolic contents which is easily neglected instead of being carefully considered. It is absolutely crucial to liberate education and spiritual development from the ritualization of pretence, and the lack of care for being rooted in culture in terms of symbolic memory. The author cites examples of Paul Ricoeur’s experiences as a dean during the student revolt, Joseph Chałasiński’s analysis of the “intelligentsia ghetto” and its relation to the authority, as well as specific approaches to Andrew Kiev’s masterpieces. Czeslaw Milosz, and Martin Heidegger turn out to have been crucial for the understanding of authority for the author of the article.